Guldfabriken - Setterblad, Mårten (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2007)
This is not a Magazine. But a Degree Project for a Master of Science at the Department of Landscape Planning at SLU Alnarp. The project concerns Guldfabriken, a real estate in Malmö. Guldfabriken is currently transforming, both in content and appearance. The transformation of the building is manifested physically through fresh plaster on the outside, new broad glass panels and a redesigned interior. The identity of Guldfabriken is changing. So is the context of the site: Malmö is growing, and Guldfabriken´s area Västra hamnen changes rapidly through the current urban development. The change of a specific site is very much what this Degree Project is about. In focus stands an inner yard that is to be developed.